ANALISIS GC-MS (GASS CROMATOGRAPHY-MASS SPECTROMETRY) TERHADAP BATANG KELAPA SAWIT (Elaeis guineesis Jaq.) - Susi Indriani; Isdaryanti Isdaryanti; Monika Agustia; Andi Besse Poleuleng; Nur Jihad Syahra; Yulius Budi Prastiyo (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2023)
Oil palm is the plant that produces the highest oil among other plants and the level of cholesterol compounds contained in palm oil is relatively lower compared to other plants. Therefore, this study aims to determine the content of compounds contained in oil palm plants using the GC-MS instrument. The results of the GC-MS analysis on the sample carried out showed that 14 peaks were detected representing 11 compound components. Based on the analysis of 11 compound components, three compounds were found that had the most significant percent area value, namely the compound 2-Propenoic acid, 1,7,7-trimethylbicyclo[2.2.1]hept-2-yl ester, exo- by 39.06%; Isobornyl propionate compound by 16.21% and the last compound is Cyclopentanecarboxylic acid, 3-methylene-,1,7,7-trimethylbicyclo[2.2.1]hept-2-yl ester (CAS) CYCLOPENTANIC with a percent area value of 12.99%.